New data on the poorly-known Dinaric cave-dwelling species Lithobius remyi Jawłowski, 1933 (Chilopoda: Lithobiomorpha: Lithobiidae) - Stojanović, Dalibor Z (Biologia Serbica, 2024)
The endemic Dinaric centipede Lithobius remyi Jawłowski, 1933, one of the rarest cave-dwelling centipedes in the Balkan Peninsula, is recorded for the first time in Serbia. An adult male from Karamakaz Cave in the Serbian Autonomous Province of Kosovo and Metohija was discovered in a private collection. The specimen is briefly described and illustrated with all taxonomically important morphological features. The currently known geographical distribution of the species is shown on the map.